A meta-analysis of the effects of plyometric training on muscle strength and power in martial arts athletes - Qin Yuan; Nuannuan Deng; Kim Geok Soh (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Plyometric training (PT) was explored as an effective intervention for enhancing muscle strength and power. However, its specific impact on these attributes in martial arts athletes had not been systematically evaluated. Therefore, the objective of this meta-analysis was to provide a quantitative assessment of the impact of PT on muscle strength and power in martial arts athletes. Additionally, it aimed to investigate potential moderators that could influence this relationship. Methods A systematic literature search was conducted across several databases, including SPORTDiscus, PubMed, CNKI, Scopus, and Web of Science Core Collection. Studies were included if they were controlled trials that examined the effects of PT on measures of muscle strength and/or muscle power in martial arts athletes. Effect sizes (ESs) were calculated using a random-effects model based on weighted and averaged standardized mean differences. Moderator analyses were performed for variables related to age and training. The ROB2 and ROBINS-I tools were used to assess the methodological quality of the included studies. Publication bias was evaluated using funnel plots and the extended Egger’s test. Results The analysis included fifteen studies with a total of 499 participants aged 12 to 24 years. The findings indicated that PT had a small-to-moderate effect on muscle strength (ES = 0.62; 95% CI = 0.38 to 0.87, p < 0.001) and power (ES = 0.45; 95% CI = 0.20 to 0.71, p = 0.001). Furthermore, neither age nor training parameters significantly moderated the effect of PT on muscle strength and power. Conclusions The findings of the present study indicated that PT effectively enhanced muscle strength and power in martial arts athletes. However, additional trials are recommended to determine the optimal training doses and further explore the interactions among training variables to improve muscle strength and power in these athletes. Trial registration https//www.crd.york.ac.uk/prospero/display_record.php? Record ID = 579,901, identifier CRD42024579901.